Molecular pathways associated with the nutritional programming of plant-based diet acceptance in rainbow trout following an early feeding exposure. (December 2016) - Balasubramanian, Mukundh; Panserat, Stephane; Dupont-Nivet, Mathilde; Quillet, Edwige; Montfort, Jerome; Le Cam, Aurelie; Medale, Francoise; Kaushik, Sadasivam; Geurden, Inge
Abstract Background The achievement of sustainable feeding practices in aquaculture by reducing the reliance on wild-captured fish, via replacement of fish-based feed with plant-based feed, is impeded by the poor growth response seen in fish fed high levels of plant ingredients. Our recent strategy to nutritionally program rainbow trout by early short-term exposure to a plant-based (V) diet versus a control fish-based (M) diet at the first-feeding fry stage when the trout fry start to consume exogenous feed, resulted in remarkable improvements in feed intake, growth and feed utilization when the same fish were challenged with the diet V (V-challenge) at the juvenile stage, several months following initial exposure. We employed microarray expression analysis at the first-feeding and juvenile stages to deduce the mechanisms associated with the nutritional programming of plant-based feed acceptance in trout. Results Transcriptomic analysis was performed on rainbow trout whole fry after 3 weeks exposure to either diet V or diet M at the first feeding stage (3-week), and in the whole brain and liver of juvenile trout after a 25 day V-challenge, using a rainbow trout custom oligonucleotide microarray. Overall, 1787 (3-week + Brain) and 924 (3-week + Liver) mRNA probes were affected by the early-feeding exposure. Gene ontology and pathway analysis of the corresponding genes revealed that nutritional programming affects pathways of sensory perception, synaptic transmission, cognitive processes and neuroendocrine peptides in the brain; whereas in the liver, pathways mediating intermediary metabolism, xenobiotic metabolism, proteolysis, and cytoskeletal regulation of cell cycle are affected. These results suggest that the nutritionally programmed enhanced acceptance of a plant-based feed in rainbow trout is driven by probable acquisition of flavour and feed preferences, and reduced sensitivity to changes in hepatic metabolic and stress pathways. Conclusions This study outlines the molecular mechanisms in trout brain and liver that accompany the nutritional programming of plant-based diet acceptance in trout, reinforces the notion of the first-feeding stage in oviparous fish as a critical window for nutritional programming, and provides support for utilizing this strategy to achieve improvements in sustainability of feeding practices in aquaculture.